Current Approach of Functioning Head and Neck Paragangliomas: Case Report of a Young Patient with Multiple Asynchronous Tumors - Alejandro Terrones-Lozano; Alan Hernández-Hernández; Edgar Nathal Vera; Gerardo Yoshiaki Guinto-Nishimura; Jorge Luis Balderrama-Bañares; Claudia Ramírez-Rentería; Judith de la Serna-Soto; Alfredo Adolfo Reza-Albarran; Lesly Portocarrero-Ortiz (Case Reports in Endocrinology)
Introduction. Pheochromocytomas (Pheo) and paragangliomas (PGL) are rare neuroendocrine tumors arising from chromaffin cells of the adrenal medulla and from the extra-adrenal autonomic paraganglia, respectively. Only 1–3% of head and neck PGL (HNPGL) show elevated catecholamines, and at least 30% of Pheo and PGL (PCPG) are associated with genetic syndromes caused by germline mutations in tumor suppressor genes and proto-oncogenes. Clinical Case. A 33-year-old man with a past medical history of resection of an abdominal PGL at the age of eleven underwent a CT scan after a mild traumatic brain injury revealing an incidental brain tumor. The diagnosis of a functioning PGL was made, and further testing was undertaken with a PET-CT with 68Ga-DOTATATE, SPECT-CT 131-MIBG, and genetic testing. Discussion and Conclusion. The usual clinical presentation of functioning PCPG includes paroxistic hypertension, headache, and diaphoresis, sometimes with a suggestive family history in 30–40% of cases. Only 20% of PGL are located in head and neck, of which only 1–3% will show elevated catecholamines. Metastatic disease is present in up to 50% of cases, usually associated with a hereditary germline mutation. However, different phenotypes can be observed depending on such germline mutations. Genetic testing is important in patients with PCPG since 31% will present a germline mutation. In this particular patient, an SDHB gene mutation was revealed, which can drastically influence the follow-up plan and the genetic counsel offered. A multidisciplinary approach is mandatory for every patient presenting with PCPG.